Effects of Tai Chi on essential hypertension and related risk factors: A meta-analysis of randomized controlled trials - Yuanyuan Guan; Yang Hao; Yun Guan; Hongwu Wang (Medical Journals Sweden, 2020)
Background: Physical exercise is an important part of hypertension management. The impact of different training styles and durations of tai chi on essential hypertension has not been evaluated to date. Objective: To analyse the influence of tai chi on blood pressure and related risk factors in patients with essential hypertension. Methods: A systematic review to assess the existing literature on the impact of tai chi in patients with essential hypertension. Randomized controlled trials were identified in Chinese and English databases to study the impact of tai chi on essential hypertension. Two reviewers selected studies independently of each other. Qualified trials were selected and their methodological quality critically evaluated. Results: Thirteen trials were included in the analysis. Following tai chi there was a significant difference between intervention and control groups with regard to change in systolic blood pressure (SBP) (weighted mean difference  = −6.58, 95% confidence interval (95% CI) (−8.14, −5.02), p = 0.005) and diastolic blood pressure (DBP) (standardized mean difference = −0.57, 95% CI (−0.77, −0.37), p < 0.0001). Taking into account the subgroup analyses, the combined results showed that 24-movement or yang-style tai chi significantly reduced both systolic and diastolic blood pressure over a period <  12 weeks or >  12 weeks in all studies. However, other styles of tai chi did not significantly reduce systolic or diastolic blood pressure after a duration <  12 weeks. Conclusion: Tai chi is an effective physical exercise in treating essential hypertension compared with control interventions. Different training durations and styles have different effects. Further randomized controlled trials are needed into the use of tai chi for the treatment and prevention of essential hypertension and other related chronic diseases.